Influence of sodium on the properties of sol-gel derived hydroxyapatite powder and porous scaffolds - Sopyan, Lis; Pusparini, Erlani; Subramaniam, Ramesh T.; Tan, Chou Yong; Ching, Yernchee; Wong, Yinhow; Zainal Abidin, Nor Ishida; Chandran, Hari; Ramesh, S.; Bang, Lethi (2017)
This study investigates the properties of sol-gel derived sodium (Na)-doped hydroxyapatite (HA) powder. Different amounts of Na (1, 5, 10 and 15 mol%) were prepared and the sintered bodies were characterized to determine the current phases, microstructural evolution and mechanical properties. X-ray diffraction analysis reveals that a phase pure HA of crystallite sizes, which varied from 35 nm to 65 nm, was obtained in the synthesized powder after calcining from 500 °C to 1000 °C. Scanning electron microscopy examination shows evidence of larger particle sizes, particularly in samples that contain higher amounts of Na concentration. The resultant powders were subsequently used to prepare porous NA-doped HA bodies through a polymeric sponge method. The addition of 5% Na resulted in a porous body with 27% porosity and was beneficial in enhancing the compressive strength of HA 17-fold compared with undoped HA. The prepared scaffold also shows suitable pore interconnectivity with pore sizes that vary between 100 and 300 μm which is suitable for use as porous bone substitutes.